Hollow Carbon Microspheres/MnO2 Nanosheets Composites: Hydrothermal Synthesis and Electrochemical Behaviors - Fan, Hui-li; Ran, Fen; Zhang, Xuan-xuan; Song, Hai-ming; Niu, Xiao-qin; Kong, Ling-bin; Kang, Long (Nano-Micro Letters, 2014)
This article reported the electrochemical behaviors of a novel hollow carbon microspheres/manganese dioxide nanosheets (micro-HC/nano-MnO2) composite prepared by an in situ self-limiting deposition method under hydrothermal condition. The results of scanning electron microscopy reveal that MnO2 nanosheets homogeneously grow onto the surface of micro-HC to form a loose-packed microstructure. The quantity of MnO2 required in the electrode layer has thereby been reduced significantly, and higher specific capacitances have been achieved. The micro-HC/nano-MnO2 electrode presents a high capacitance of 239.0 F g−1 at a current density of 5 mA cm−2, which is a strong promise for high-rate electrochemical capacitive energy storage applications.